Mapping the electrostatic force field of single molecules from high-resolution scanning probe images - Hapala, Prokop; Švec, Martin; Stetsovych, Oleksandr; van der Heijden, Nadine J; Ondráček, Martin; van der Lit, Joost; Mutombo, Pingo; Swart, Ingmar; Jelínek, Pavel (Nature communications, 2016)
How electronic charge is distributed over a molecule determines to a large extent its chemical properties. Here, we demonstrate how the electrostatic force field, originating from the inhomogeneous charge distribution in a molecule, can be measured with submolecular resolution. We exploit the fact that distortions typically observed in high-resolution atomic force microscopy images are for a significant part caused by the electrostatic force acting between charges of the tip and the molecule of interest. By finding a geometrical transformation between two high-resolution AFM images acquired with two different tips, the electrostatic force field or potential over individual molecules and self-assemblies thereof can be reconstructed with submolecular resolution.